Isozyme-Specific Role of SAD-A in Neuronal Migration During Development of Cerebral Cortex. (11th October 2018) - Nakanishi, Keiko; Niida, Hiroyuki; Tabata, Hidenori; Ito, Tsuyoshi; Hori, Yuki; Hattori, Madoka; Johmura, Yoshikazu; Yamada, Chisato; Ueda, Takashi; Takeuchi, Kosei; Yamada, Kenichiro; Nagata, Koh-ichi; et al.
Abstract: SAD kinases regulate presynaptic vesicle clustering and neuronal polarization. A previous report demonstrated that Sada −/− and Sadb −/− double-mutant mice showed perinatal lethality with a severe defect in axon/dendrite differentiation, but their single mutants did not. These results indicated that they were functionally redundant. Surprisingly, we show that on a C57BL/6N background, SAD-A is essential for cortical development whereas SAD-B is dispensable. Sada −/− mice died within a few days after birth. Their cortical lamination pattern was disorganized and radial migration of cortical neurons was perturbed. Birth date analyses with BrdU and in utero electroporation using pCAG-EGFP vector showed a delayed migration of cortical neurons to the pial surface in Sada −/− mice. Time-lapse imaging of these mice confirmed slow migration velocity in the cortical plate. While the neurites of hippocampal neurons in Sada −/− mice could ultimately differentiate in culture to form axons and dendrites, the average length of their axons was shorter than that of the wild type. Thus, analysis on a different genetic background than that used initially revealed a nonredundant role for SAD-A in neuronal migration and differentiation.